A Seepage Control Cutoff in an Extreme Saline Environment - Iván Contreras; Jon Ausdemore; Rachel Leier; Aaron Grosser; Amr Ragy; Kevin Green (Deep Foundations Institute, 2016)
"Construction of a new tailings dam was required to increase tailings storage capacity at a trona mine near Green River, Wyoming. The new dam was founded on overburden soils underlain by both fractured and competent bedrock. The stored tailings and water had high salt content, resulting in salty seepage water. To reduce the impact of the salty water on groundwater and the Green River, the design of the new tailings dam included a 257,260 SF (23,900 m2) seepage cutoff extending into competent rock.An extensive subsurface characterization was performed prior to completing the design and suitable seepage cutoff methods were evaluated. The approach selected was a full replacement panel using hydromill and clamshell for construction and self-hardening slurry (SHS) for the wall material. Laboratory testing was performed and ongoing monitoring has continued to evaluate the hydraulic conductivity and seepage cutoff performance in the briny environment.The paper includes project background, the collaborative approach and outcomes of the QA/QC program, and the monitoring results for the seepage cutoff wall.PROJECT BACKGROUNDCiner Wyoming, LLC (formerly OCI Wyoming, LLC) owns and operates the Big Island Mine facility near Green River, Wyoming. This underground trona mine has produced soda ash since 1962. The Greater Green River Basin covers much of southwestern Wyoming and extends into northeastern Utah and northwestern Colorado. The Ciner facility is located in the Green River Basin, which is part of the Wyoming Basin physiographic province. The Green River runs to the west and the south of the Ciner facility.Beginning in the early 1990s, Ciner primarily disposed tailings underground in mined-out panels. However, in recent years, underground storage has become limited and some disposal has transitioned to the ground surface. Long-term planning revealed a need to expand Ciner’s surface tailings disposal capabilities. Pond 2, a previously permitted disposal area, was identified as the most viable location for a storage facility. The Pond 2 site is directly north of the Ciner plant facilities, northwest of the active Upper Delta tailings storage facility, and northeast of the Green River (Fig 1)."